Strength Institutional and Normative Framework to Implement Effective Capacity Building Actions: A Critical Regional Analysis - Bautista-Hernáez, Andrés (My University, 2018)
The implementation of United Nations Sustainable Development Goals and the agenda 2030 is a challenge for international community as a whole. However, acknowledging the importance of universal set of rules, the main role in implementing such Goals falls to States. In this regard, it is of vital importance an appropriate consistency and strength of regional rules, principles and policies that would be applicable at the national level. This research analyses these characteristics by examination of disaster capacity-building regulations. We will focus on the strength and coherence of institutional and normative frameworks at regional level and how States implement them.
Keywords: Desarrollo sostenible; International disaster law; Sustainable development